Urbanization, Biodiversity and Ecosystem Services: Challenges and Opportunities: A Global Assessment - Elmqvist, Thomas (Springer Nature, 2013)
Urban Ecology; Urbanism; Sustainable Development; Complex Systems; Science, general; International Environmental Law